2022
DOI: 10.1590/s1678-9946202264063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eleven immunochromatographic assays for SARS-CoV-2 detection: investigating the dengue cross-reaction

Abstract: COVID-19 disease is spread worldwide and diagnostic techniques have been studied in order to contain the pandemic. Immunochromatographic (IC) assays are feasible and a low-cost alternative especially in low and middle-income countries, which lack structure to perform certain diagnostic techniques. Here we evaluate the sensitivity and specificity of eleven different IC tests in 145 serum samples from confirmed cases of COVID-19 using RT-PCR and 100 negative serum samples from blood donors collected in February … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The assumption of cross-reaction between SARS-CoV-2 and DENV was reported in several studies. However, most of these studies have built this assumption based on the antigenic cross-reactivity using the LFA and a few based on ELISA results detecting NS1 antigens [9][10][11][12]. Therefore, we investigated the possible serological cross-reaction between SARS-CoV-2 and DENV us- ing more advanced serological assays, which are the CL-900i automated analyzer and the ELISA test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption of cross-reaction between SARS-CoV-2 and DENV was reported in several studies. However, most of these studies have built this assumption based on the antigenic cross-reactivity using the LFA and a few based on ELISA results detecting NS1 antigens [9][10][11][12]. Therefore, we investigated the possible serological cross-reaction between SARS-CoV-2 and DENV us- ing more advanced serological assays, which are the CL-900i automated analyzer and the ELISA test.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported serological crossreactivity of the immune responses between SARS-CoV-2 and DENV [2,9]. Most of the available studies are based on point-of-care rapid testing kits [11][12][13][14]. However, some rapid test kits have low specificity and can generate false positives [15].…”
Section: Introductionmentioning
confidence: 99%